2019
DOI: 10.17305/bjbms.2019.4501
|View full text |Cite
|
Sign up to set email alerts
|

Androgen effect on connexin expression in the mammalian female reproductive system: a systematic review

Abstract: The functions of androgen and connexin in the mammalian female reproductive system are suggested to be related. Previous research has shown that androgen affects connexin expression and localization in the female reproductive system, altering its function. However, no definitive conclusion on their cause-effect relationship has been drawn yet. In addition, a high prevalence of women with polycystic ovary syndrome (PCOS), who are characterized by elevated androgen levels and failure of ovulation, has prompted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Steroids (estrogens and androgens) are actively involved in placental functions and pathologies [ 25 , 26 ]. It has been shown that DVL1 and DVL3 proteins could regulate placental aromatase expression and the aromatase gene transcription [ 27 ] that regulate human trophoblast differentiation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroids (estrogens and androgens) are actively involved in placental functions and pathologies [ 25 , 26 ]. It has been shown that DVL1 and DVL3 proteins could regulate placental aromatase expression and the aromatase gene transcription [ 27 ] that regulate human trophoblast differentiation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, androgen may also have an effect on GJs ( Mohd Kamal et al, 2019 ). Clinical studies in PCOS patients have found a correlation between androgen and connexin expression, the expression of CX43 also increased in cultured granulosa cells by adding androstenedione, but the specific regulatory mechanisms have not been studied.…”
Section: Hormonal Regulation Of Intercellular Communication In Cocmentioning
confidence: 99%
“…AR activation affects the level of connexins, proteins that form gap junctions between granulosa cells and the oocyte and hence regulate intracellular communication; a prerequisite for folliculogenesis [19]. There is evidence connecting AR and connexins 37 and 43, the main connexins involved in granulosa-oocyte communication [19]. Although not conclusive, AR may induce connexin expression, whereas high levels of AR activation, or AR antagonism, can decrease the levels of expression [19].…”
Section: Evidence Supporting This Ker 641 Biological Plausibilitymentioning
confidence: 99%
“…Additionally, the AR may regulate folliculogenesis indirectly by interacting with proteins important to the process. These proteins include Insulin Growth Factor (IGF1) and its receptor (IGFR1), follicle-stimulating hormone receptor (FSHR), anti-Müllerian hormone (AMH) and connexins essential for oocyte-granulosa cell communication [14,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%